Assessment of natural radioactivity (40K, 238U and 232Th) and radiological risk in building construction materials: the case of Benin hill granites - Mahougnon Zinsou; Naivo Naivo RABESIRANANA; Daton MEDENOU; Martin RASOLONIRINA; Bertin Bertin GBAGUIDI; Guy MENSAH (Brazilian Journal of Radiation Sciences, 2024)
Continuous exposure to ionizing radiation can have harmful effects on human health. In this respect, a study was carried out in the Communes of Dassa-zoume and Glazoue to determine the levels of 40K, 238U and 232Th in granites and sand. The specific activities obtained made it possible to assess the possible radiological risks associated with the resident population. During sampling work in November 2022, twelve granite samples were taken from twelve quarries. In addition, a sand sample was collected in Cotonou for comparison. All samples were then sent to the INSTN-Madagascar laboratory for gamma-ray spectrometry analysis using a NaI(TI) detector. The results show that the average specific activities of 40K, 238U and 232Th in the granites are (1329 ± 128) Bq.kg-1, (44 ± 11) Bq.kg-1 and (129 ± 44) Bq.kg-1 respectively. Those in sand are (144 ± 8) Bq.kg-1, (30 ± 2) Bq.kg-1 and (56 ± 7) Bq.kg-1 respectively. The average equivalent radium activity is (330 ± 74) Bq.kg-1 versus (122 ± 10) Bq.kg-1 for sand. The mean gamma index for granite was (1.2 ± 0.3), compared with (0.43 ± 0.03) for sand. The average absorbed dose rate in air is (153.4 ± 9.4) nGy.h-1 versus (53.7 ± 5.1) nGy.h-1 for sand. For adults, for 80% building occupancy factor, the mean annual indoors and outdoors effective dose (E) inside a building are (0.75 ± 0.05) mSv.y-1 and (0.19 ± 0.01) mSv.y-1 versus (0.26 ± 0.05) mSv.y-1 and (0.07 ± 0.01) mSv.y-1 for sand. For 60% factor, the means are (0.56 ± 0.03) mSv.y-1 and (0.38 ± 0.02) mSv.y-1 versus (0.20 ± 0.01) and (0.13 ± 0.01) mSv.y-1 for sand. For the children, for a building occupancy factor of 80%, the average E are (0.86 ± 0.05) mSv.y-1 and (0.21 ± 0.01) mSv.y-1 versus (0.30 ± 0.01) mSv.y-1 and (0.08 ± 0.01) mSv.y-1 for sand respectively for indoors and outdoors. For infants, the E are (1.00 ± 0.06) mSv.y-1 and (0.25 ± 0.01) mSv.y-1 versus (0.35 ± 0.01) mSv.y-1 and (0.09 ± 0.01) mSv.y-1 for sand respectively for indoors and outdoors. For children, for a building occupancy factor of 60%, the average E are (0.64 ± 0.03) mSv.y-1 and (0.43 ± 0.02) mSv.y-1 versus (0.23 ± 0.01) mSv.y-1 and (0.15 ± 0.01) mSv.y-1 for sand respectively indoors and outdoors. For infants, for a building occupancy factor of 60%, the E are (0.75 ± 0.05) mSv.y-1 and (0.50 ± 0.02) mSv.y-1 versus (0.26 ± 0.01) mSv.y-1 and (0.18 ± 0.01) mSv.y-1 for sand respectively indoors and outdoors. For adults, the excess lifetime cancer risk at age 66 for a total annual effective dose induced by granite is (3.1 ± 0.01).10-3 versus (1.1 ± 0.01).10-3 for sand. For the children and infants, the average ELCR is (3.5 ± 0.01)E-3 and (4.1 ± 0.01)E-3 versus (1.2 ± 0.01)E-3 and (1.4 ± 0.01)E-3 for sand respectively. Statistical analysis of the data was performed with Python 3.11 and R 4.3.2 on the Spyder and studio interface. The p-value is < 0.001 compared with the UNSCEAR reference value for absorbed dose rate in air, effective dose and excess risk, which are 84 nGy.h-1, 0.48 mSv.y-1 and 0.29.10-3. This shows that the granites in the quarries studied present a radiological risk when used as building materials and need specific radiation protection measures for his users.